2021
DOI: 10.2298/tsci191228025l
|View full text |Cite
|
Sign up to set email alerts
|

Dropping in electrospinning process: A general strategy for fabrication of microspheres

Abstract: The dropping mechanism in the electrospinning process is elucidated. A moving jet becomes thinner at the initial stage due to the acceleration caused by the electrostatic force. When the jet diameter reaches a threshold, beyond which the jet breaks into drops and daughter jets, dropping occurs. The drops will finally form microspheres. Effects of applied voltage, flow rate, polymer?s concentration and receptor?s distance on the dropping process are theoretically analyzed and experimentally ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The general approaches to fabricating smooth nanofibers are electrospinning ( Gao et al, 2021 ; Liu et al, 2021 ) and bubble electrospinning ( He and Qian, 2022 ; Qian and He, 2022 ). However, Lin, et al, 2021 suggested a general strategy for the fabrication of unsmooth nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…The general approaches to fabricating smooth nanofibers are electrospinning ( Gao et al, 2021 ; Liu et al, 2021 ) and bubble electrospinning ( He and Qian, 2022 ; Qian and He, 2022 ). However, Lin, et al, 2021 suggested a general strategy for the fabrication of unsmooth nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…When considering different approaches to describing the formation and dissipation of fogs one should mention physico-mathematical models involving the description of turbulent processes. The latter ones are the subject of research in different areas, for example, in modeling solvent evaporation in a moving jet of the spinning process [22,23]. In the problems of describing fog formation above rivers this approach allows modeling wave-like fog patterns along the river accompanied by dissipated whirling columns of fog similar to «steam devils» [24].…”
Section: Influence Of the Relief And Formation Of Turbulent Structuresmentioning
confidence: 99%
“…The instability also occurs in some spinning process, see, for example, the following works. [10][11][12][13][14][15][16][17] In this paper, the moving jet is approximated as an axially moving cylindrical rod-like viscoelastic fluid, and its Eulerian load is studied.…”
Section: Introductionmentioning
confidence: 99%